PEMANFAATAN SEARCH ENGINE OPTIMAZION (SEO) SEBAGAI TEKNIK MARKETING PADA PENGUSAHA PEMULA GENERASI Z DI KABUPATEN TULUNGAGUNG - Shobir, Labib Muzaki (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
SEO (Search Engine Optimization) is a sales promotion technique so that the website created is ranked at the top of the search engine page or on the first page. SEO can improve the position of a site in search engines such as Google, thus also affecting traffic or visits from people who need products or services. In fact, marketing strategies using SEO are still rarely utilized due to limited access to information related to SEO and there has been no comprehensive training on the use of SEO as a marketing technique in the business. Based on these problems, online business training was conducted through the utilization of Search Engine Optimazion (SEO) as a marketing technique for generation z start-up entrepreneurs in Tulungagung Regency. The number of activity participants is 30 generation z people in Tulungagung district who are starting a business or have a business in the form of online. The method used in this service is based on the training method. Based on the activities carried out, the knowledge and skills of z generation start-up entrepreneurs in Tulungagung Regency increased. Participants gained new knowledge about the utilization of Search Engine Optimazion (SEO) who initially did not know at all became more knowledgeable, while those who had learned before gained additional knowledge. This shows that the planned training activities have been carried out well and achieved the targets that have been set..